Potential accessibility - an interesting conceptual framework to address strategic planning issues in the Amsterdam region? - Thomas Straatemeier (European Regional Science Association (ERSA), 2005)
It is difficult to prove a direct causal link between the spatial patterns of economic activities and the quality of the transport system. But it seems obvious that the transport system creates conditions, which enable economic activities to interact with each other. The concept of potential accessibility – or what and how can be reached from a given point in space within a certain travel time – can provide a useful conceptual framework to describe these conditions. For economic activities it is not the transport system itself that is important, but the fact that the transport systems provides them with access to workers, consumers et cetera. It is therefore necessary to take both the qualities of the transport system and the land-use system in to account, which is exactly what measuring potential accessibility does. Depending on the kind of economic activity you're looking at different accessibility conditions may be important. This paper investigates for the Amsterdam region the quality of the potential accessibility on different scales (global - regional – local) and compares these qualities to the spatial pattern of different economic activities to see which qualities are more favorable to certain activities then others. Creating these favorable accessibility conditions is what planners of the land-use and transport system should aim for. The paper concludes with reviewing different regional planning policies to see if this is true.
Keywords: 330